Systematic review of emergency medicine clinical practice guidelines: Implications for research and policy. - Arjun K Venkatesh; Dan Savage; Benjamin Sandefur; Kenneth R Bernard; Craig Rothenberg; Jeremiah D Schuur (PLoS ONE)
Introduction Over 25 years, emergency medicine in the United States has amassed a large evidence base that has been systematically assessed and interpreted through ACEP Clinical Policies. While not previously studied in emergency medicine, prior work has shown that nearly half of all recommendations in medical specialty practice guidelines may be based on limited or inconclusive evidence. We sought to describe the proportion of clinical practice guideline recommendations in Emergency Medicine that are based upon expert opinion and low level evidence. Methods Systematic review of clinical practice guidelines (Clinical Policies) published by the American College of Emergency Physicians from January 1990 to January 2016. Standardized data were abstracted from each Clinical Policy including the number and level of recommendations as well as the reported class of evidence. Primary outcomes were the proportion of Level C equivalent recommendations and Class III equivalent evidence. The primary analysis was limited to current Clinical Policies, while secondary analysis included all Clinical Policies. Results A total of 54 Clinical Policies including 421 recommendations and 2801 cited references, with an average of 7.8 recommendations and 52 references per guideline were included. Of 19 current Clinical Policies, 13 of 141 (9.2%) recommendations were Level A, 57 (40.4%) Level B, and 71 (50.4%) Level C. Of 845 references in current Clinical Policies, 67 (7.9%) were Class I, 272 (32.3%) Class II, and 506 (59.9%) Class III equivalent. Among all Clinical Policies, 200 (47.5%) recommendations were Level C equivalent, and 1371 (48.9%) of references were Class III equivalent. Conclusions Emergency medicine clinical practice guidelines are largely based on lower classes of evidence and a majority of recommendations are expert opinion based. Emergency medicine appears to suffer from an evidence gap that should be prioritized in the national research agenda and considered by policymakers prior to developing future quality standards.